The Collapse of the New Orde Regime Resulted in Changes in Indonesia's Economic Policy - Kelik Endro Suryono; Vicki Dwi Purnomo (Jurnal Pengabdian Masyarakat Formosa, 2022)
The reform era or the post-Suharto era in Indonesia began in 1998, to be precise when President Soeharto resigned on May 21 1998 and was replaced by the then vice president, BJ Habibie. This period was founded bya more open socio-political environment. Issues during this period included the push for democracy and a stronger civilian government, elements of the military trying to maintain influence, growing Islamism in politics and society in general, and demands for greater regional autonomy . The reform process resulted in a higher degree of freedom of speech , in contrast to the widespread censorship during the New Order . As a result, political debate has become more open in the mass media and artistic expression has increased. Events that have shaped Indonesia in this period include a series of terrorist incidents (including the 2002 Bali bombings ) and the 2004 Indian Ocean earthquake and tsunami . Using the knife of deconstruction of critical legal theory and socio-legal methodology with statutory, historical, conceptual and legal political economy approaches, three questions are raised, firstly the role of law in the market reform agenda which underlies the idea of limiting the role of the state in the economy; second, how is the role of the state in the economy being debated in the MPR and; third, what are the implications of the market reform agenda for the results of changes to the economic constitution.